The Development of Digital Teaching Materials Based on Microlearning Integrated with Flipbook to Help Students Improve Mathematical Communication Skills on the Topic of Linear Equations - Parasian Hutagaol, Hotber; Haris, Denny (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to: (1) obtain Microlearning-based digital teaching materials that are valid, practical and effective so as to improve students’ mathematical communication abilities; (2) describe the improvement of students’ mathematical communication skills through Microlearning-based digital teaching materials.The subjects in this study were class VIII-5 students of SMP Negeri 17 Medan for the academic year 2022/2023, while the objects in this study were Microlearning-based digital teaching materials on Straight Line Equations. This research is a Research & Development (R&D) research using a 4D development model namely Define, Design, Develop and Disseminate. The results of this study indicate that: (1a) Microlearning-based digital teaching materials based on the validator’s  are in the valid category with an average score for material is 3.64 and an average score for media is 3.46; (1b) Microlearning-based digital teaching materials are included in the very practical category with a teacher response score of 90.63% and an overall student response of 80.09%; (1c) Microlearning-based digital teaching materials have met the effective criteria in terms of classical learning completeness with a percentage of 85.71%, the achievement of indicators/learning objectives for each indicator has been achieved; and (2) the students’ mathematical communication  abilities increased, judging by the mathematical communication abilities of each indicator that had increased and the N-Gain value increase from the pretest and posttest obtained was 0.47 in the medium category.